2019
DOI: 10.1088/1755-1315/362/1/012092
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and Ultimate Analysis Before and After Physical & Chemical Demineralization

Abstract: In this study, a total of 12 coal samples were collected. Physical and chemical cleaning were employed on these collected coal samples. In order to understand the effect of physical & chemical cleaning on these samples, samples characterization were performed in terms of proximate and ultimate analysis. Calorific values of each corresponding clean coal samples were also determined. After chemical cleaning calorific values of each sample decreased, while chemical cleaning resulted in ultra clean coals as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…represents the elemental composition of dry Moringa Oleifera the result shows that carbon has a higher composition than any other element present in the Moringa Oleifera this is due to the amount of Carbon dioxide that the Moringa tree absorbed. The result also shows that Moringa Oleifera has less percentage of Hydrocarbonate composition, the result shows in agreement with the result found by(Mahmet, 2019) on Nitrogen composition.…”
supporting
confidence: 91%
“…represents the elemental composition of dry Moringa Oleifera the result shows that carbon has a higher composition than any other element present in the Moringa Oleifera this is due to the amount of Carbon dioxide that the Moringa tree absorbed. The result also shows that Moringa Oleifera has less percentage of Hydrocarbonate composition, the result shows in agreement with the result found by(Mahmet, 2019) on Nitrogen composition.…”
supporting
confidence: 91%
“…The study found corn-cob to have 61.2% content of cellulose and hemicellulose, making it the highest; while cotton stalk has relatively higher thermo-chemical potential due to its HHV of 19.2 MJ/kg. The most significant properties of particles during fuel combustion are volatile matter and fixed carbon contents [ 25 ]. Biomass materials are enabled for use as energy resources by these two properties because the measure of the ease with which biomass fuels can ignite and subsequently oxidize or gasify is significantly provided by the two factors [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%